Effect of Seasonal Variations and Collection Form on Antioxidant Activity of Propolis from San Juan, Argentina - Isla, Maria Ines (2009)
Propolis was included in the Argentine Food Code as a functional food. The chemical parameters and antioxidant properties of propolis samples from the same colonies of Apis mellifera in San Juan (Cuyo region, Western Argentine) were compared every month for 1 year using two collection methods. Chemical parameters were analyzed by the spectrophotometric method and fingerprinting using high-performance liquid chromatography with ultraviolet detection. The antioxidant activities of propolis samples were measured using model systems including the analysis of the scavenging activities for 2,2′-azino-bis(3- ethylbenzthiazoline-6-sulfonic acid) (ABTS) and 2,2-diphenyl-1-picrylhydrazyl (DPPH) radicals and the β-carotene bleaching assay. The results showed that propolis had a higher free radical scavenging and lipid peroxidation inhibitory capacity than butylated hydroxytoluene and quercetin, antioxidants used in the pharmaceutical and food industries. The concentration required to scavenge 50% of free radicals (SC50) values differed depending on the sample collection month. Samples collected in November had the highest antioxidant capacity. In all cases, SC50 values of propolis samples obtained by scraping were similar to those collected from a wire mesh (5μg/mL for ABTS and 20-30μg/mL for DPPH radicals). A significant positive correlation was found between the antioxidant capacity and flavonoid content of each analyzed extract. The chemical profiles were very similar. Galangin (3,5,7- trihydroxyflavone), an antioxidant compound, was detected in all samples as a major compound. The chromatographic profile suggests that of Baccharis sp., which would be one of the botanical sources of propolis from western Argentina, and the content of galangin can be used as a parameter for evaluating propolis quality. Our results suggest that Argentine propolis from Cuyo is a promising source of bioactive compounds as ingredients for developing functional foods with a beneficial impact on oxidative stress.